(untitled) (Research, Society and Development, 2022)
Nowadays, geotechnology is an extremely important tool for carrying out environmental studies through the collection of a series of data acquired by satellite images. With the help of the QGIS software and the MapBiomas Brazil color palette, the types of land use and occupation in the Tanque river watershed, MG, Brazil, have been identified. With this information, the water quality parameters were compared through the monitoring station of the Minas Gerais Institute for Water Management (IGAM) on the Tanque river (code RD080) from January 2017 to October 2020. Land use and occupation upstream of the monitoring point, seeking to describe the possible uses and occupation of the soil that may interfere with the parameters of water quality in this monitoring station, with the main uses observed being pasture (39.31%) and forest formation (35.19%). Violations of Normative Deliberation 01/2008 were observed in the analyzed parameters, which in some cases are related to seasonality (turbidity and true color, for example). Dissolved iron values ​​above the maximum allowed value were also observed in 67% of the analyses, an indication of the mining vocation of this metal in the region, which interfered with the quality of the water. E. coli showed violations in 40% of the analyses, which seems to be related to cattle and horses in the basin, whose main land use is pasture.